Highly improved pH-Responsive anticancer drug delivery and T2-Weighted MRI imaging by magnetic MOF CuBTC-based nano/microcomposite - Gharehdaghi, Zahra; Naghib, Seyed Morteza; Rahimi, Rahmatollah; Bakhshi, Atin; Kefayat, Amirhosein; shamaeizadeh, Armin; Molaabasi, Fatemeh (Frontiers in Molecular Biosciences, 2023)
Cu-BTC framework has received a considerable attention in recent years as a drug carrier candidate for cancer treatment due to its unique structural properties and promising biocompatibility. However, its intrinsic deficiency for medical imaging potentially limits its bioapplications; To address this subject, a magnetic nano/microscale MOF has been successfully fabricated by introducing Fe3O4 nanoparticles as an imaging agent into the porous isoreticular MOF [Cu3(BTC)2] as a drug carrier. The synthesized magnetic MOFs exhibits a high loading capacity (40.5%) toward the model anticancer DOX with an excellent pH-responsive drug release. The proposed nanocomposite not only possesses large surface area, high magnetic response, large mesopore volume, high transverse relaxivity (r2) and good stability but also exhibits superior biocompatibility, specific tumor cellular uptake, and significant cancer cell viability inhibitory effect without any targeting agent. It is expected that the synthesized magnetic nano/microcomposite may be used for clinical purposes and can also serve as a platform for photoactive antibacterial therapy ae well as pH/GSH/photo-triple-responsive nanocarrier.